Notes of statement by Sir William Beveridge to General Council at their meeting on 16 December, 1942 - Beveridge, William Henry Beveridge, Baron, 1879-1963
1942-12-17 1942 1940s 9 pages 8. households 5/- or 6/- below that figure. He thought it might be desirable to make some adjustment in the rate of benefit and contributions in London. He thought that was a point for consideration. Mr. Wolstencroft asked what would be the position of a man who went from London to a country district. Sir William Beveridge said that was one of the administrative difficulties against the suggestion. He thought a man would draw the rate of the district in which he was actually living. If he had been living in London and then went out of London to a district where the rent was much lower, he wouldn't get the higher benefit. Mr. Bussey pointed out that a person who had contributed the higher rate for a long time and then moved out of London would be penalised. Sir William Beveridge pointed out that there would be no differentiation in regard to retirement pensions. After all everyody [everybody] knew when old age was coming and could plan ahead. Miss Hancock raised the position of widows' pensions. She said she was thinking of the woman of about 50 who had no young children. She said it might be difficult for her to get a medical certificate to say she was incapable of work, and she may not be the type of woman who could turn to something entirely fresh. Sir William Beveridge agreed that they had taken a rather severe line about widows. He wanted every widow without encumbrances and able to work to feel she ought to do it until she got to retiring age. He agreed that all widows might not be able to do factory work, but he thought most widows could do domestic work. He said he did not mean that a husband ought not to be able to provide for his widow to give up work and to live without work at all, but he thought that was a matter for voluntary insurance. Mr. Bagnall pointed out that there was no provision made for the widow while she was qualifying for unemployment benefit. 292/150.5/5/2